Evaluation of reverse logistics sectoral agreements as mechanisms for promoting the circular economy - Leal, Thomas Leonardo Marques de Castro; Araújo, Janaina Cajé Guerra de; Rodrigues, Luciano Brito (Brazilian Journal of Production Engineering, 2025)
The National Solid Waste Policy (PNRS) and Reverse Logistics (RL) are aligned with the principles of the Circular Economy (CE). However, this study aims to assess whether the Sectoral Agreements (SA) for Waste Reverse Logistics, provided in PNRS, contribute to the development of a more circular economy. Firstly, it was necessary to define the foundations of CE through a systematic review of other reviews. After analyzing 36 articles, it was possible to describe 9 CE themes related to life cycle, resource use, design and waste recovery. The SAs were evaluated to determine whether they aligned with the themes or not. The results show that the Agreements comply with the legislation in terms of stakeholder responsibility, but do not favor CE. The one that came closest to EC CE was the Agreement of lubricant oil packaging, by introducing recycled material into the manufacture of new products. There is plenty of room for improvement in SAs to make the reverse waste cycle more circular, such as industrial symbiosis, eco-design, life cycle extension and circular business models.